Respostas

2014-03-15T20:20:59-03:00
Primeiro acharemos a razão dessa pa 
Rpa = a2 - a1
Rpa = 2 - (-5)
Rpa = 7 
Depois jogaremos na formula
an = a1 + (n - 1) . r                     a1 = primeiro numero
                                                 n = o numero desejado
                                                  r = razão da pa (Rpa)
an = -5 + (5 -1) * 7
an = -5 + 28
an = 23
2014-03-15T20:31:27-03:00
A1= -5
An= a5
R = 7
n= 5

An= A1 + (n-1)r
A5= -5 +( 5-1) . 7
A5 = -5 + 4 . 7
A5 = -5 + 28
A5 = 23